Effect of intermittent extracellular low-pH environment on human umbilical vein endothelial cell activity - Ryota Nishida; Tomoaki Fukui; Kenichi Sawauchi; Yohei Kumabe; Hyuma Kondo; Yuya Yamamoto; Kyohei Takase; Ryo Yoshikawa; Takahiro Niikura; Ryosuke Kuroda; Keisuke Oe (PLoS ONE, 2025)
Transcutaneous CO2 application promotes fracture healing and osteogenesis via angiogenesis. However, its molecular mechanism remains unclear. This therapy transiently decreases intra-tissue pH in the affected area to approximately 7.0 for 20 min, followed by recovery. We hypothesized that such intermittent pH changes activate endothelial cells similarly to acidic preconditioning. We aimed to investigate the response of human umbilical vein endothelial cells (HUVECs) to daily intermittent low-pH stimulation. HUVECs were cultured under three conditions: daily 20-min exposure to a low-pH medium (approximately 7.0), followed by a return to a control medium (approximately 7.4) (Change group); continuous exposure to a low-pH medium (Low pH group); constant culturing in a control medium (Control group). Cell proliferation, tube formation, migration, and protein/gene expression were assessed. Tube formation and migration were significantly enhanced in the Change group compared with those in the Control group, and tube formation was also increased in the Low pH group. Western blotting revealed upregulated expression of vascular endothelial growth factor (VEGF) and VEGF receptor 2 in the Change group. CD31 gene expression was elevated in the Low pH and Change groups on Days 1 and 7, respectively. Phosphorylated extracellular signal-regulated kinases 1 and 2 (ERK1/2) and protein kinase B (AKT) levels in the Low pH and Change groups were significantly increased compared with those in the Control, except for ERK2 in the Low pH group. The suppression of ERK1/2 or AKT by their inhibitors (U0126 and LY294002, respectively) during low-pH exposure inhibited proliferation and tube formation, indicating that the ERK1/2 mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3 kinase (PI3K)/AKT pathways mediate endothelial cell activation in response to intermittent acidic stimulation. Intermittent low-pH exposure enhanced HUVEC activity, mediated by the ERK1/2 MAPK and PI3K/AKT pathways. Our findings provide insights into the mechanism by which transcutaneous CO2 application promotes angiogenesis and tissue repair.